A Retrospective Review of the Outcomes and Utility of Percutaneous Radiofrequency Rhizotomy for Trigeminal Neuralgia Using Anatomic Landmark Guidance in Asleep Patients. (16th November 2020) - Stone, Lauren E; Falowski, Steven M
Graphical Abstract: